Xạ trị hậu phẫu ung thư vú: kinh nghiệm một số ca bệnh đầu tiên - Hiệp, Đoàn Trung; Bách, Trần Bá; Long, Nguyễn Đình; Sơn, Hà Ngọc; Nam, Nguyễn Văn; Hân, Nguyễn Văn; Hiếu, Nguyễn Trung (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
.